Generation of a Recombinant Anticarsia Gemmatalis Multicapsid Nucleopolyhedrovirus Expressing a Foreign Gene under the Control of a Very Late Promoter - Arana, Eloisa Irene (2001)
A recombinant Anticarsia gemmatalis multicapsid nucleopolyhedrovirus (AgMNPV) expressing β-galactosidase under the control of the polyhedrin promoter was generated in our laboratory. To this end, we cloned the AgMNPV-2D genomic DNA fragment containing the polh gene and subcloned and sequenced the polyhedrin gene and its flanking regions. Based on this sequence information, sets of primers were designed to amplify the flanking regions by PCR, including appropriate restriction sites. The transfer vector (pAgPHZ) was constructed by the consecutive cloning of these PCR fragments flanking the Escherichia coli LacZ gene, in place of the polh gene. pAgPHZ was used for cotransfection of UFL-AG-286 insect cells with AgMNPV-2D DNA and the required recombinant, generated by homologous recombination with the polh locus, was identified by its polh⁻/LacZ⁺ plaque phenotype. Its genome structure was confirmed by PCR, restriction digestion and Southern blot analyses. The kinetics and levels of expression of β-galactosidase in UFL-AG-286 cells infected with the recombinant were tested by SDS-PAGE and enzymatic activity assays.